Case report of repeat thrombolytic therapy in patient with acute circular-apical myocardial infarction, complicated anginous status - D. V. Bosikov; N. V. Stepanova; V. E. Tarasova; Yu. M. Botnar (Евразийский Кардиологический Журнал)
Presented clinical case report illustrates nonstandart approach use repeat thrombolytic therapy patient 49 y.o. with acute circular – apical myocardial infarction, after noneffective primary systemic thrombolytic therapy rtPA. Moreover, repeat thrombolytic therapy in hospital stage was vital alternative in case with significant tamely delay mechanical reperfusion. After 90 minutes then introduction rtPA has been done, we got negative dynamic on ECG in the form of additional ST-segment elevation at other (early intact) lead, and reccurent anginous pain refractory to standard doses narcotic analgesic. In connection with remote PCI – center, we supposed significant tamely deIlay to mechanical reperfusion. In view of this factors, high risk to undesired event, refractory anginous pain, we made decision of repeat thrombolytic therapy with non-immunogenic staphilokinase, and it has been effective. At a later time the disease is taking it’s normal course.